ANALISIS EFEKTIVITAS PROGRAM TRAINING HEARTIST DAN KOMUNIKASI VERBAL TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA NOVOTEL BALI NUSA DUA BADUNG BALI) - Anak Agung Ayu Mirah Kencanawati; I Komang Mahayana Putra; Ni Wayan Sukartini; I Made Sarjana (STIMI Handayani Denpasar, 2021)
The Research aims to analyze the effectiveness of the Heartist Training Program and Verbal communication towards employee performance at Novotel Bali Nusa Dua. Using the simple random sampling technique through the formula Slovin got respondents as many as 72 employees of Novotel Bali Nusa Dua. The analytical techniques used are descriptive statistical analyses. Based on the results of this study is that the minimum value of a variable training program heartist (X1) is 26 and a maximum value of 37, with an average value of 31.95 and a standard deviation of 2.89. The communication variable (X2) has a minimum value of 15 and a maximum value of 23, with an average value of 19.62 and a standard deviation of 2.23. The employee (Y) performance variable has a minimum value of 25 and a maximum value of 33, with an average value of 29.26 and a standard deviation of 2.52. This suggests that training and verbal communication programs are important factors in improving employee performance. The effectiveness of both factors became an effort in the company.